Deciphering the molecular basis of ammonium uptake and transport in maritime pine. (12th February 2016) - Castro‐Rodríguez, Vanessa; Assaf‐Casals, Iman; Pérez‐Tienda, Jacob; Fan, Xiaorong; Avila, Concepción; Miller, Anthony; Cánovas, Francisco M.
Abstract: Ammonium is the predominant form of inorganic nitrogen in the soil of coniferous forests. Despite the ecological and economic importance of conifers, the molecular basis of ammonium uptake and transport in this group of gymnosperms is largely unknown. In this study, we describe the functional characterization of members of the AMT gene family in Pinus pinaster : PpAMT1.1, PpAMT1.2 and PpAMT1.3 (subfamily 1) and PpAMT2.1 and PpAMT2.3 (subfamily 2). Our phylogenetic analysis indicates that in conifers, all members of the AMT1 subfamily evolved from a common ancestor that is evolutionarily related to the ancient PpAMT1.2 gene. Individual AMT genes are developmentally and nutritionally regulated, and their transcripts are specifically distributed in different organs. PpAMT1.3 was predominantly expressed in the roots, particularly during N starvation and mycorrhizal interaction, whereas PpAMT2.3 was preferentially expressed in lateral roots. Immunolocalization studies of roots with varied nitrogen availability revealed that PpAMT1 and PpAMT2 proteins play complementary roles in the uptake of external ammonium. Heterologous expression in yeast and Xenopus oocytes revealed that the AMT genes encode functional transporters with different kinetics and with different capacities for ammonium transport. Our results provide new insights on how nitrogen is acquired and transported in conifers. Abstract : Ammonium is the predominant form of inorganic nitrogen in the soil of coniferous forests. Despite the ecological and economic importance of conifers, the molecular basis of ammonium uptake and transport in this group of gymnosperms is largely unknown. In this study, we describe the functional characterization of members of the AMT gene family in Pinus pinaster : PpAMT1.1, PpAMT1.2 and PpAMT1.3 (subfamily 1) and PpAMT2.1 and PpAMT2.3 (subfamily 2). Our phylogenetic analysis indicates that in conifers, all members of the AMT1 subfamily evolved from a common ancestor that is evolutionarily related to the ancient PpAMT1.2 gene. Individual AMT genes are developmentally‐ and nutritionally‐regulated and their transcripts are specifically distributed in different organs. PpAMT1.3 was predominantly expressed in the roots, particularly during N starvation and mycorrhizal interaction whereas PpAMT2.3 was preferentially expressed in lateral roots. Immunolocalization studies of roots with varied nitrogen availability revealed that PpAMT1 and PpAMT2 proteins play complementary roles in the uptake of external ammonium. Heterologous expression in yeast and Xenopus oocytes revealed that the AMT genes encode functional transporters with different kinetics and with different capacities for ammonium transport. Our results provide new insights on how nitrogen is acquired and transported in conifers.